Gravity Data Analysis for Fault Identification and Earthquake Hypocentre Relocation Using Modified Joint Hypocentre Determination Method in Cianjur Area - Divia Isyania Putri; Suwondo; Mohammad Iqbal Tawakal; Tati Zera; Sutrisno Sutrisno (Indonesian Journal on Geoscience, 2026)
An earthquake with a magnitude of M 5.6 occurred in Cianjur, West Java, on November 21st, 2022, and left 321 people dead. This event raised concerns about the potential for aftershocks, necessitating an in-depth analysis to evaluate future seismic risk in Cianjur. This study aims to identify the type of fault that triggered the earthquake and to relocate the hypocentre in the Cianjur area. First horizontal derivative (FHD) and second vertical derivative (SVD) methods from gravity data were used for mapping the fault structure and the fault type. Fault location is represented by zero SVD and peak FHD to determine the type of fault; the maximum FHD and minimum SVD values were compared. The correlation results of FHD and SVD graphs obtained a fault line with a northwest to southeast direction on the Cugenang Fault and Cimandiri Fault line, with its movement direction from Pelabuhan Ratu with a shear fault type. The results of the relocation analysis show the existence of two identified alignment structures in the direction of north northeast ̶ south southeast (NNW ̶ SSE) and east northeast to west-southwest (WSW-ENE) which form a group on the trendline of the fault zone, as evidenced by the tectonic activity in the Cianjur area caused by the existence of a pair of mutually perpendicular horizontal faults (shear conjugate faults).